Toll-like receptor chaperone HSP90B1 and the immune response to Mycobacteria. - Andrew D Graustein; Elizabeth A Misch; Munyaradzi Musvosvi; Muki Shey; Javeed A Shah; Chetan Seshadri; Augustine Ajuogu; Kathryn Bowman; Humphrey Mulenga; Ashley Veldsman; Willem A Hanekom; Mark Hatherill; et al. (PLoS ONE, 2018)
Rationale HSP90B1, also known as gp96, is a chaperone for multiple Toll-like receptors (TLRs) and is necessary for TLR-mediated inflammatory responses in murine myeloid cells. The molecule is also expressed in T-cells though its specific role is unknown. We hypothesized that human HSP90B1 regulates monocyte and T-cell responses to Mycobacterium tuberculosis (Mtb) and bacilli Calmette-Guerin (BCG) and that its variants are associated with susceptibility to TB disease. Methods We screened 17 haplotype-tagging SNPs in the HSP90B1 gene region for association with BCG-induced T-cell cytokine responses using both an ex-vivo whole blood assay (N = 295) and an intracellular cytokine staining assay (N = 180) on samples collected 10 weeks after birth. Using a case-control study design, we evaluated the same SNPs for association with TB disease in a South African pediatric cohort (N = 217 cases, 604 controls). A subset of these SNPs was evaluated for association with HSP90B1 expression in human monocytes, monocyte-derived dendritic cells, and T-cells using RT-PCR. Lastly, we used CRISPR/Cas9 gene editing to knock down HSP90B1 expression in a human monocyte cell line (U937). Knockdown and control cell lines were tested for TLR surface expression and control of Mtb replication. Results We identified three SNPs, rs10507172, rs10507173 and rs1920413, that were associated with BCG-induced IL-2 secretion (p = 0.017 for rs10507172 and p = 0.03 for rs10507173 and rs1920413, Mann-Whitney, dominant model). SNPs rs10507172 and rs10507173 were associated with TB disease in an unadjusted analysis (p = 0.036 and 0.025, respectively, dominant model) that strengthened with sensitivity analysis of the definite TB cases, which included only those patients with microbiologically confirmed Mtb (p = 0.007 and 0.012, respectively). Knockdowns of HSP90B1 in monocyte cell lines with CRISPR did not alter TLR2 surface expression nor influence Mtb replication relative to controls. Conclusion Among infants, an HSP90B1 gene-region variant is associated with BCG-induced IL-2 production and may be associated with protection from TB disease. HSP90B1 knockdown in human monocyte-like cell lines did not influence TLR2 surface localization nor Mtb replication. Together, these data suggest that HSP90B1 regulates T-cell, but not monocyte, responses to mycobacteria in humans.